PERAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK TERHADAP KINERJA GURU (Studi Pada SMA Negeri Wilayah Pemalang Selatan) - Haryono, Haryono (Jurnal Mahasiswa Pasca Sarjana, 2018)
This study aims to examine, test and analyze whether the principal role oftransformational leadership and organizational culture moderates the intrinsic motivation onteacher performance.Population and sample are high school teachers in the State Pemalang south by 110people. The research data is primary data collected directly from the respondents to thequestionnaire. The research method used Moderation Regression Analisys (MRA)-type quasimoderator, The method of data analysis using computer software approach with SPSS forWindows version 19.The results showed that the role of transformational leadership strengthens the influenceof intrinsic motivation on teacher performance, as well as weaken the influence of organizationalculture on the performance of teachers' intrinsic motivation.Keywords: transformational leadership principals, organizational culture, intrinsic motivation,teacher performance